Process formulation and packaging of vacuum fried saba (Musa Sapientum Linn. var Compressa)banana chips - Asis, Ma. Concepcion Priscilla Claraval (1997)
Fully mature banana fruits of (approximately 4 days after harvest) saba variety was processed into chips by vacuum frying under a pressure of 76 psi. The product was evaluated for its physic-chemical properties and sensory attributes. Results showed that the best time and temperature combination was 120oC for 7 minutes. The product has a yellowish color, is moisture content was 0.243% (dry basis), Aw of 0.49 at 25oC and fat content of 39.75% (dry basis). The formulated product was packed under two (2) different packaging conditions: gas flushing with nitrogen and vacuum packing, in aluminum foil laminate (PP/foil/PE). The product was packed in polyethylene bag which serve as control. Storage stability of the samples was determined for a period of seven (7) weeks. Microbiological, physico-chemical and sensory evaluation were performed weekly for the same period. Results of analysis showed that gas flushed banana chips in PP/foil/PE laminate had the highest overall acceptability. Its sensory attributes of color, odor, texture, and flavor were rated high.